Various remediation measures for groundwater contamination - Ojha A.; Tiwary D. (My University, 2025)
Groundwater pollution remediation involves three remedial approaches: containment, i.e. preventing the contamination migration and exposure; active restoration, i.e. removal and treatment of the contamination; and natural attenuation through biological, naturally occurring chemical, or physical degradation processes so that contaminant is converted to harmless species. The chapter will be focusing on the various preventive as well as remedial techniques to combat groundwater pollution. Biological treatment techniques (bioaugmentation, bioventing, biosparging, bioslurping, and phytoremediation) will be discussed along with chemical (ozone and oxygen gas injection, chemical precipitation, membrane separation, ion exchange, carbon absorption, aqueous chemical oxidation, and surfactant enhanced recovery [SER]) and physical (pump and treat, air sparging, and dual phase extraction) techniques in detail. While nanotechnology is growing exponentially in playing an important role in environmental issues, it is slowly creeping into treatment of polluted groundwater. Carbon nanotubes (CNTs) and zero-valent iron nanoparticles have been extensively studied in this context. The chapter will also focus on these nanomaterials and provide deep insight into them. © 2021 John Wiley & Sons Ltd. All rights reserved.